2011
DOI: 10.1038/aps.2011.102
|View full text |Cite
|
Sign up to set email alerts
|

Berberine protects against lipopolysaccharide-induced intestinal injury in mice via alpha 2 adrenoceptor-independent mechanisms

Abstract: Aim: To investigate the mechanisms responsible for the protective action of berberine (Ber) against gut damage in endotoxemic mice. Methods: Male BALB/c mice were administered intragastrically with distilled water (0.1 mL/10 g), Ber (50 mg/kg) alone, yohimbine (2 mg/kg) alone, or Ber (50mg/kg) in combination with yohimbine (2 mg/kg) for 3 d. On the third day, lipopolysaccharide (LPS, 18 mg/kg) or normal saline was intraperitoneally injected one hour after the intragastric administration. Following the treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 33 publications
5
28
0
Order By: Relevance
“…Previous studies have demonstrated that BBR acts as an LPS antagonist and blocks LPS/TLR4 signaling in an LPS-induced animal model (28)(29)(30). Li et al (30) reported that BBR protects against LPS-induced intestinal injury in mice via reducing enterocyte apoptosis, inhibiting the TLR4 pathway and decreasing neutrophil infiltration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that BBR acts as an LPS antagonist and blocks LPS/TLR4 signaling in an LPS-induced animal model (28)(29)(30). Li et al (30) reported that BBR protects against LPS-induced intestinal injury in mice via reducing enterocyte apoptosis, inhibiting the TLR4 pathway and decreasing neutrophil infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that BBR acts as an LPS antagonist and blocks LPS/TLR4 signaling in an LPS-induced animal model (28)(29)(30). Li et al (30) reported that BBR protects against LPS-induced intestinal injury in mice via reducing enterocyte apoptosis, inhibiting the TLR4 pathway and decreasing neutrophil infiltration. Huang et al (29) reported that BBR exerted a potent anti-inflammatory effect by suppressing the LPS-evoked secretion of the proinflammatory cytokines IL-1β, IL-6 and TNFα and attenuated the activation of LPS-TLR4-cytokines/NF-κB signaling pathways in the mouse macrophage-like cell line RAW264.7.…”
Section: Discussionmentioning
confidence: 99%
“…As a major component of RC, BBR has drawn extensive attention recently because of its wide range of effects such as antiinflammatory, lipid-lowering, anti-tumor, and anti-diabetic effects, among others [2][3][4][5] . In vivo studies have revealed that berberrubine (BRB) is the primary metabolite of 9-demethylated BBR that may have potential pharmacological activities [6] .…”
Section: Introductionmentioning
confidence: 99%
“…In support of this, it was reported that berberine induced IL-12 p40 production in macrophages, at least in part, through the a2-adrenergic receptor (Kang et al, 2002). On the other hand, berberine protected against LPS-induced intestinal or lung injury via a2-adrenergic receptor-independent mechanisms (Zhang et al, 2008;Li et al, 2011). Hence, the role of the a2-adrenoceptor or GRP 40 in berberine-induced suppression of PKCd-HuR activation needs to be examined.…”
Section: Discussionmentioning
confidence: 93%